Milestones in archives administration in Nigeria (2012)
This paper examines the development of archives administration in Nigeria, beginning with the early efforts of the Colonial Office in London to preserve the official record of the Nigerian Secretariat. It then discusses in detail Dr Kenneth Dike's record survey of the 1950s which laid the foundation for the establishment of the Nigerian Record Office (later known as the National Archives) and traces the development of archives administration at the national and state level as well as in the business sector. Finally, it examines the legislation for archives management in Nigeria, identifying a number of issues that must be addressed.